Alcohol Consumption at Midlife and Risk of Stroke During 43 Years of Follow-Up: Cohort and Twin Analyses. Issue 3 (March 2015) - Kadlecová, Pavla; Andel, Ross; Mikulík, Robert; Handing, Elizabeth P.; Pedersen, Nancy L.
Abstract : Background and Purpose—: Although alcohol–stroke association is well known, the age-varying effect of alcohol drinking at midlife on subsequent stroke risk across older adulthood has not been examined. The effect of genetic/early-life factors is also unknown. We used cohort and twin analyses of data with 43 years of follow-up for stroke incidence to help address these gaps. Methods—: All 11 644 members of the population-based Swedish Twin Registry born 1886 to 1925 with alcohol data aged ⩽60 years were included. The interaction of midlife alcohol consumption by age at stroke was evaluated in Cox-regression and analyses of monozygotic twins were used. Covariates were baseline age, sex, cardiovascular diseases, diabetes mellitus, stress reactivity, depression, body mass index, smoking, and exercise. Results—: Altogether 29% participants developed stroke. Compared with very-light drinkers (<0.5 drink/d), heavy drinkers (>2 drinks/d) had greater risk of stroke (hazard ratio, 1.34; P =0.02) and the effect for nondrinkers approached significance (hazard ratio, 1.11; P =0.08). Age increased stroke risk for nondrinkers ( P =0.012) and decreased it for heavy drinkers ( P =0.040). Midlife heavy drinkers were at high risk from baseline until the age of 75 years when hypertension and diabetes mellitus grew to being the more relevant risk factors. In analyses of monozygotic twin-pairs, heavy drinking shortened time to stroke by 5 years ( P =0.04). Conclusions—: Stroke-risk associated with heavy drinking (>2 drinks/d) in midlife seems to predominate over well-known risk factors, hypertension and diabetes, until the age of ≈75 years and may shorten time to stroke by 5 years above and beyond covariates and genetic/early-life factors. Alcohol consumption should be considered an age-varying risk factor for stroke.